The genesis, reception, and aftermath of the créolité movement in the Francophone Caribbean: Creole identity and creolisation re-examined - Sam Coombes (Francosphères)
In this article, the debates surrounding the créolité movement are reassessed from the perspective of more recent and contemporary events in Antillean intellectual and political life. Following a critical re-examination of the origins of the créolité movement, the culturally particularist drive of the work of the creolist writers is relativised by way of discussion of other intellectuals (Condé, Ménil, Walcott) from the region whose outlooks and relationship to the Antillean cultural heritage differs markedly from it. Crucially, it is argued that whereas the advocates of créolité became trapped in excessive cultural parochialism, the movement's rejection has led certain of its critics to dilute the specificity of Antillean culture and the postcolonial inheritance in a universality which edged dangerously close to that of globalisation. The thought of Martiniquan intellectual Edouard Glissant, it is contended, offers a route out of the impasse, one which is both culturally rooted and internationalist at the same time.Cet article propose un réexamen des débats autour de la créolité à travers le prisme d'événements récents dans la vie intellectuelle et politique antillaise. Mon argumentation s'appuie sur un réexamen critique des origines du mouvement créoliste, qui permet de mettre en perspective les tendances particularistes de certains auteurs de la région en les contrastant avec la pensée d'autres intellectuels antillais (Condé, Ménil, Walcott) dont le rapport à l'héritage antillais diffère de façon radicale. Cette démarche permettra de montrer comment les défenseurs de la créolité sombrèrent dans un particularisme excessif, tandis que d'un autre côté le rejet du mouvement a conduit certains critiques à perdre de vue la spécificité antillaise et l'héritage colonial qui se sont trouvés dissouts dans un universalisme dangereusement proche de la mondialisation. Je montrerai notamment que la pensée de l'intellectuel martiniquais Edouard Glissant permet de sortir de cette impasse en ouvrant une voie ancrée sur le plan culturel, mais ouverte à une pensée plus internationale.